Effect of Conjunctive Application of Rock Phosphate, Pyrites and Farm Yard Manure on Physical Properties of Alfisols and Yield of Wheat (Triticum aestivum L.) - Yadav, R S; Lavti, D L; Yadav, B L; Baser, B L (Annals of Arid Zone, 2016)
A tield experiment was conducted during 1995-96 rabi season on Agronomy Farm. Rajasthan College of Agriculture. Udaipur to find out the most effective combination of com posted rock phosphate pyrite for improving the physical properties of soil and wheat yield. Results indicated that increase in acidulation of rock phosphate with pyrite as well as FYM improved the soil physical condition and increased grain and straw yield of wheat. The application of rock phosphate pyrite in the proportion of 1:3 was proved best for its effectiveness on water stable aggregates . >0.25 mm (40.64%). WHC (56.23%) and saturated hydraulic conductivity (2.21 cm h -1). as well as on physico-chemical properties and grain and straw yield of wheat. The treatment RP + pyrite in the proportion of 1:3, composted with FYM also gave highest net return (Rs. 30140.50 ha -1). The highest benefit: cost ratio was observed under treatment RP + pyrite in the proportion of 1:3 without FYM.